Development and validation of a high performance liquid chromatography quantification method of levo‐tetrahydropalmatine and its metabolites in plasma and brain tissues: application to a pharmacokinetic study. (9th October 2016) - Abdallah, Inas A.; Huang, Peng; Liu, Jing; Lee, David Y.; Liu‐Chen, Lee‐Yuan; Hassan, Hazem E.
Abstract: Levo ‐tetrahydropalmatine (l‐ THP) is an alkaloid isolated from Chinese medicinal herbs of the Corydalis and Stephania genera. It has been used in China for more than 40 years mainly as an analgesic with sedative/hypnotic effects. Despite its extensive use, its metabolism has not been quantitatively studied, nor there a sensitive reliable bioanalytical method for its quantification simultaneously with its metabolites. As such, the objective of this study was to develop and validate a sensitive and selective HPLC method for simultaneous quantification ofl‐ THP and its desmethyl metabolitesl‐ corydalmine (l‐ CD) andl‐ corypalmine (l‐ CP) in rat plasma and brain tissues. Rat plasma and brain samples were processed by liquid–liquid extraction using ethyl acetate. Chromatographic separation was achieved on a reversed‐phase Symmetry® C18 column (4.6 × 150 mm, 5 μm) at 25°C. The mobile phase consisted of acetonitrile–methanol–10 mm ammonium phosphate (pH 3) (10:30:60, v /v) and was used at a flow rate of 0.8 mL/min. The column eluent was monitored at excitation and emission wavelengths of 230 and 315 nm, respectively. The calibration curves were linear over the concentration range of 1–10, 000 ng/mL. The intra‐ and interday reproducibility studies demonstrated accuracy and precision within the acceptance criteria of bioanalytical guidelines. The validated HPLC method was successfully applied to analyze samples from a pharmacokinetic study ofl‐ THP in rats. Taken together, the developed method can be applied for bioanalysis ofl‐ THP and its metabolites in rodents and potentially can be transferred for bioanalysis of human samples.